A Review of Hypertension and Diabetes Protocols for Medical Service Trips (MSTs) in Latin America and the Caribbean - Christopher Dainton; Jenifer Truong; Charlene H. Chu (Ubiquity Press, 2018)
Background: Hypertension and diabetes are among the most common chronic conditions that may be managed on short-term, primary care medical service trips (MSTs) in Latin America and the Caribbean (LAC), but the quality of patient care delivered remains unclear. Objective: This study summarizes protocols that Western volunteer clinicians use in managing these patients, and highlights their commonalities, differences, and potential limitations. Methods: A systematic web search was used to identify organizations operating MSTs in LAC. Organizations were contacted by email or through their websites to obtain clinical protocols intended for use on their brigades. These protocols were qualitatively analyzed, and recommendations were categorized into clinical assessment, non-pharmacologic recommendations, and pharmacologic recommendations. Findings: Two hundred twenty-five organizations were identified and contacted, and protocols were obtained for 20 of these. Eleven (55%) of these protocols discussed hypertension, and 10 (50%) discussed diabetes. Only one protocol provided any literature support for its recommendations. Conclusions: The analyzed protocols may give insight into context-specific realities of practice on MSTs, but they often neglected key aspects of clinical management that are emphasized in international guidelines. This study is an initial step in clinical guidelines development for MSTs operating in LAC.